COVID-19 and public transport: an overview and recommendations applicable to Latin America - Carlos Felipe Pardo (Asociación Colombiana de Infectología, 2021)
The article presents a general overview on COVID-19 transmission in the context of public transport, particularly applicable to decision making in Latin America. Based on recent findings on COVID-19 transmission and the relative importance of each factor (droplets, fomites, and aerosol routes) in such transmission, we seek to update the discussion on the topic that has generally been based on social distance as the only parameter for reducing the risk of transmission and broadens the vision to integrate ventilation, users' behavior (mask and eye protection use, silence while in the transport system) and travel distance. Recommendations to improve mobility conditions reducing the risk of COVID-19 contagion are provided.